A Different Kind of Christmas Tree: Anomalous Origin of the Right Coronary Artery from the Pulmonary Artery (ARCAPA). Issue 2 (18th October 2013) - Afolabi‐Brown, Olayinka; Witzke, Christian; Moldovan, Raul; Pressman, Gregg
<x xml:space="preserve">Abstract</x> Anomalous right coronary artery from the pulmonary artery (ARCAPA) is a rare congenital coronary anomaly that has an incidence of 0.002%. We report a case of a previously healthy female who presented to our hospital with pneumonia and was incidentally discovered to have ARCAPA. This was initially diagnosed on echocardiography by the unusual echocardiographic finding of multiple color flow Doppler signals around the right ventricular free wall and apex which were subsequently confirmed by angiography to be due to extensive collateral circulation between the left and right coronary arteries. This represents an unusual echocardiographic manifestation of this very rare condition.